Probing the resonant states of Cl2 using velocity slice imaging. (24th November 2015) - Gope, Krishnendu; Prabhudesai, Vaibhav S; Mason, Nigel J; Krishnakumar, E
Abstract: The negative ion resonances in molecular chlorine are probed using velocity slice imaging of the Cl − fragment produced in dissociative electron attachment (DEA). The capability of the velocity slice imaging to cover the entire 360° allows us to obtain clear evidence for the presence of the resonance in the 2.5 eV DEA peak along with the presence of The resonance is expected to be the contributor only to the 0 eV DEA peak. Its presence in the 2.5 eV DEA peak calls for a relook at the theoretical calculations which have not identified any resonance in the 2.5 eV peak. We also identify the presence of the and resonances in the 5.6 eV peak. The momentum images indicate no signature of a resonant contribution in the dipolar dissociation region up to 80 eV.